Can Web-Based AI Be Implemented in the Middle School Science Classroom? A Critical Review - Azari, Anetta Mutiara; Rochintaniawati, Diana; Agustin, Rika Rafikah (Jurnal Inovasi Pendidikan IPA, 2024)
This literature review examines the effect of artificial intelligence (AI) on science education, particularly in middle schools, and addresses both its limitations and future directions. This review critically assesses the potential implications of AI on science learning in middle school. It does so by examining 17 Scopus-indexed studies. The review reveals significant positive outcomes regarding how web-based AI-powered education affects students' learning outcomes, technological skills, and better decision-making. Despite these promising results, this article recognizes the possible dangers and difficulties associated with implementing AI in the classroom, such as limited access to technology in the region, reliance on AI, and ethical considerations when using AI-generated content. Solutions such as expanding technological knowledge and encouraging critical thinking are proposed to address these issues, anticipating the danger of bias and ethics toward AI. The conclusion of this review indicates that AI implementation in science learning has significant potential benefits despite limitations and challenges. In addition, this review also guides students, educators, and AI developers on optimizing AI's educational benefits.